Anastomotic Biliary Stricture Development after Liver Transplantation in the Setting of Retained Prophylactic Intraductal Pediatric Feeding Tube: Case and Review - Patrick T. Koo; Valentina Medici; James H. Tabibian (Case Reports in Hepatology)
The biliary anastomosis remains a common site of postoperative complications in liver transplantation (LT). Biliary complications have indeed been termed the “Achilles’ heel” of LT, and while their prevention, diagnosis, and treatment have continued to evolve over the last two decades, various challenges and uncertainties persist. Here we present the case of a 33-year-old man who, 10 years after undergoing LT for idiopathic recurrent intrahepatic cholestasis, was noted to have developed pruritus and abnormalities in serum liver biochemistries during routine post-liver transplant follow-up. Abdominal ultrasound revealed a linear, 1.5 mm hyperechoic filling defect in the common bile duct; magnetic resonance cholangiopancreatography demonstrated a curvilinear filling defect at the level of the choledochocholedochostomy, corresponding to the ultrasound finding, as well as an anastomotic biliary stricture (ABS). On endoscopic retrograde cholangiography (ERC), a black tubular stricture with overlying sludge was encountered and extracted from the common bile duct, consistent with a retained 5 Fr pediatric feeding tube originally placed at the time of LT. The patient experienced symptomatic and biochemical relief and successfully underwent serial ERCs with balloon dilatation and maximal biliary stenting for ABS management. With this case, we emphasize the importance of ensuring spontaneous passage or removal of intraductal prostheses placed prophylactically at the time of LT in order to minimize the risk of chronic biliary inflammation and associated sequelae, including cholangitis and ABS formation. We also provide herein a brief review of the use of prophylactic internal transanastomotic prostheses, including biliary tubes and stents, during LT.